Exploring the use of Facebook in developing EFL skills and student leadership - Huy, Nguyen Quoc; Bao, Dat (English Language Teaching Educational Journal, 2025)
As social media becomes deeply embedded in the lives of young learners, English language educators are increasingly exploring its pedagogical potential. This article examines how Facebook can function as a multifunctional learning ecosystem that supports three key dimensions of EFL development: learner engagement, leadership growth, and humour competence. Drawing on reflective teaching practice and autoethnographic insights, the study synthesizes experiences from multiple classroom contexts in which Facebook was integrated into homework tasks, collaborative projects, and creative, meme-based activities. The findings reveal that Facebook fosters authentic communication, encourages active participation, and enables students to assume leadership roles through managing group discussions, organising challenges, and moderating peer interactions. Additionally, the strategic use of memes helps develop humour competence, a linguacultural and communicative skill often overlooked in language teaching. Despite challenges such as distractions, privacy concerns, and misinformation, the study demonstrates that when guided by clear pedagogical intentions, Facebook can serve as a holistic learning environment that enhances language proficiency, soft skills, and digital literacy. Implications are offered for educators seeking to integrate social media meaningfully into EFL instruction.